PEMIKIRAN KRITISISME DAN REFORMISME KONTEMPORER DALAM TEORI PENDIDIKAN ISLAM KONTEMPORER - Lestari, Liza Puji; Sukardi, Ismail; Astuti, Mardiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The rapid development of globalization demands that Muslims adapt to modern challenges in science, technology, and socio-cultural aspects. This article aims to analyze the concepts of contemporary criticism and reformism within Islamic education theory, focusing on the ideas of Ibrahim Abu Rabi and Tariq Ramadan. Utilizing a literature review method, this study explores criticism, emphasizing the importance of critical thinking and the synthesis of rationalism and empiricism, alongside reformism, which advocates for gradual societal changes toward inclusivity and justice. The findings highlight that Abu Rabi emphasizes the integration of modern knowledge and spiritual values to shape morally grounded individuals, while Tariq Ramadan advocates for education based on universal values, intercultural dialogue, and curriculum reform aligned with global challenges. The study recommends adopting multidisciplinary approaches, problem-based learning, and strengthening character education within contemporary Islamic education. In conclusion, integrating Islamic values with modern approaches can enhance the relevance of Islamic education in shaping a critical, inclusive, and socially responsible generation.